2018
DOI: 10.3390/molecules23102632
|View full text |Cite
|
Sign up to set email alerts
|

Unsymmetrical Spiroalkanedithiols Having Mixed Fluorinated and Alkyl Tailgroups of Varying Length: Film Structure and Interfacial Properties

Abstract: A custom-designed series of unsymmetrical spiroalkanedithiols having tailgroups comprised of a terminally fluorinated chain and a hydrocarbon chain of varying lengths were synthesized and used to prepare self-assembled monolayers (SAMs) on gold substrates. The specific structure of the adsorbates was of the form [CH3(CH2)n][CF3(CF2)7(CH2)8]C[CH2SH]2, where n = 7, 9, and 15 (designated as F8H10-C10, F8H10-C12, and F8H10-C18, respectively). The influence of the length of the hydrocarbon chain in the bidentate di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 93 publications
0
21
0
Order By: Relevance
“…Fluorocarbon chains are known to cause disruption in inter-chain packing [14]. While hydrocarbon chains present a linear structure, perfluorinated chains form helical structure and therefore self-assemble in less compact and more disordered layers [15].…”
Section: Wettability and Effect On The Resistance To Highly Acidic Elmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorocarbon chains are known to cause disruption in inter-chain packing [14]. While hydrocarbon chains present a linear structure, perfluorinated chains form helical structure and therefore self-assemble in less compact and more disordered layers [15].…”
Section: Wettability and Effect On The Resistance To Highly Acidic Elmentioning
confidence: 99%
“…We also present preliminary results of the application of SAM layers as a patterned resist to plate thin lines of nickel, nickel here being meant to become an adhesion layer prior to copper plating. 12,12,13,13,14,14,15,15,15,15-nonafluoropentadecylphosphonic acid (fC15-PA), 12,12,13,13,14,14,15,15,16,16,17,17-tridecafluoroseptadecylphosphonic acid (fC17-PA), 12,12,13,13,14,14,15,15,16,16,17,17,18,18,19,19,19-Heptadecafluorononadecylphosphonic acid(fC19-PA), and 10,11-Bis (2,2,3,3,4,4,5,5,6,6,7,7,8,8,…”
mentioning
confidence: 99%
“… 41 − 44 Only recently, Chinwangso and co-workers demonstrated the ability to generate films with controlled interfacial heterogeneity by linking two chemically dissimilar chains—a hydrocarbon chain with a partially fluorinated chain or an oligo(ethylene glycol) chain—on a bidentate spiroalkanedithiol (SADT) head group, as illustrated in Figure 1 . 30 , 38 − 40 , 45 …”
Section: Introductionmentioning
confidence: 99%
“…The enhanced stability of bidentate thiol-based SAMs on gold arises from the entropydriven "chelate effect" [31]. Another advantage of bidentate adsorbates is the ability to incorporate two different terminal groups into the same molecule, which offers flexibility in film composition, allowing the generation of unique nanoscale interfaces composed of phase-incompatible chemical entities [34,35]; these "conflicted" interfaces are comprised of chemically disparate species held in close proximity [34,35,[38][39][40][41]. Recently, we reported that "conflicted" SAM-based interfaces generated from bidentate spiroalkanedithiols possessing mixed hydrocarbon and fluorocarbon tailgroups exhibit enhanced protein resistance when compared to SAMs generated from their single-component monodentate counterparts [41].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that "conflicted" SAM-based interfaces generated from bidentate spiroalkanedithiols possessing mixed hydrocarbon and fluorocarbon tailgroups exhibit enhanced protein resistance when compared to SAMs generated from their single-component monodentate counterparts [41]. Moreover, the generation of SAMs from dithiol-based adsorbates permits studies of the behavior and properties of interfaces consisting of homogeneously mixed disparate chemical species [38][39][40][41] that would typically phase-separate to form surfaces having patches of single-component domains [42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%